Hubungan self efficacy dan prestasi belajar siswa pada mata pelajaran ilmu pengetahuan alam terpadu - Try Susanti (IJER (Indonesian Journal of Educational Research), 2016)
Abstrak Tujuan penelitian ini adalah untuk meneliti hubungan antara kepercayaan diri (self-efficacy) dan prestasi akademik siswa pada sekolah menengah. Sampel penelitian ini berjumlah 37 orang siswa sekolah tahun akademik 2014/2015 yang dipilih dengan teknik total sampling. Pengukuran kepercayaan diri (self – efficacy) menggunakan skala The Teacher Efficacy Scale, sedangkan pengukuran prestasi siswa menggunakan nilai rata-rata rapor siswa. Analisis data menggunakan korelasi product moment. Hasil penelitian menunjukkan kepercayaan diri (self-efficacy) diri siswa memiliki hubungan dengan prestasi akademik siswa pada mata pelajaran ilmu pengetahuan alam terpadu (Biologi). Semakin tinggi kepercayaan diri (self efficacy) siswa, semakin tinggi prestasi mereka, sebaliknya semakin rendah kepercayaan diri (self-efficacy) siswa maka semakin rendah prestasi akademik mereka pada mata pelajaran ilmu pengetahuan alam (Biologi). Kata kunci: Self Efficacy, Prestasi, Siswa Abstract [Relationship between self-efficacy and academic achievement in science subjects (Biology)].The aim of the study was to investigate the relation between self-efficacy and academic achievement in high school students. In this study, 37 students in the academic year 2014/2015 were selected by means of total sampling. To measure self efficacy, The Teacher Efficacy Scale was used. To measure achievement score grade point average (school report) in classes was used. To analyze data product moment correlation analysis was used. Analysis of data revealed that self –efficacy are correlated with academic achievement in Biology. The higher the students' self efficacy, the higher the student achievement in science subject (Biology). Conversely, the lower the students' self-efficacy, the lower the learning achievements of students in science subjects (Biology). Keywords: Sel -f Efficacy, Achievement, Student